Influência da adição de fibras alimentares em salsicha de frango com redução de gordura sobre as propriedades tecnológicas e sensoriais - Henck, Jenifer Mayara Monari [UNESP] (2016)
Among the non-meat ingredients with functional properties, dietary fiber has emerged as a fat substitute in emulsified and cooked chicken products, due to improvements in both the technological and sensory properties. In this context, the aim of this study was to evaluate the effect of the addition of soluble and insoluble dietary fibers on the technological and sensory characteristics of emulsified and cooked chicken products containing mechanically deboned meat. Three soluble dietary fibers (inulin, fructooligosaccharides and alpha-cyclodextrin) and two insoluble (oat fiber and wheat fiber) were added in proportions of 3 and 6% to emulsified and cooked chicken products with fat reduction. Two control formulations were also prepared, C1 with 10% fat and no added dietary fiber and C2 with no fat and no added dietary fiber. Response surface methodology was used to evaluate the addition of alpha-cyclodextrin fiber and wheat fiber to chicken sausage with fat reduction. The emulsified and cooked chicken products were analyzed for chemical composition, yield, emulsion stability, pH, instrumental color, texture profile and stability to lipid oxidation. For the chicken sausage, the microbiological stability and microstructure were also evaluated and sensory analysis. The alpha-cyclodextrin showed the greatest emulsifying capacity, improved emulsion stability and the yield of emulsified and cooked chicken product with fat reduction. Wheat fiber increased the hardness and both wheat fiber and oat fiber, in the larger proportion, increased chewiness. The fat reduction resulted in decreasing lightness of the emulsified and cooked chicken products but it did not affect the a* and b* values. Both alpha-cyclodextrin fiber and wheat fiber had an effect on the hardness and the chewiness of chicken sausages with mechanically deboned chicken. The best chicken sausage formulation with fat reduction was T2 showing that it was possible to add 8,98% dietary fiber (8,54% alpha-cyclodextrin and 0,44% wheat fiber) with good sensory results. The alpha-cyclodextrin fiber showed great potential as a fat substitute in chicken frankfurter sausages with good technological and sensory results.